Inkless multi-color writing and copying of laser-programmable photonic crystals. Issue 5 (7th April 2020) - Wang, Yunlong; Zhao, Qilong; Du, Xuemin
Abstract : Shape-memory-polymer-based photonic crystals can be precisely programmed by a NIR laser at the nanoscale, resulting in multi-color writing and copying capabilities. Abstract : Rewritable papers, as environmentally friendly alternatives for information delivery, hold great promise to reduce the abundant use of ordinary papers that cause severe environmental problems. In recent decades, photonic crystals (PCs) have shown great potential in developing rewritable papers. However, existing PC papers still confront many challenges, including poor storage stability, short-cycle lifetime, monotonous colors, and absence of copying capability. Herein, we report the fabrication of a rewritable PC paper based on programmable configurations of a synthesized shape memory polymer (SMP). The resulting SMP-based PC paper does not need additional inks and can be facilely used to write by the near- infrared (NIR) light with assistance from a pre-printed black paper as a photothermal layer. Heating from the black paper induces various stable configurations of the PCs, thus creating multiple colors in the irradiated areas. Moreover, the PC paper possesses excellent colorful copying capability that can transform information from a paper with pre-printed black letters or complex images via scanning with NIR light. These images can be stably stored for more than 6 months at ambient conditions, which can be even erased and rewritten over 50 times without significant loss in color quality. This environment-friendly SMP-based PC paper with extraordinary properties holds great promise in the fields of next-generation office papers, smart price tags, and anti-counterfeiting labels.